AngularJS directives cookbook : extend the capabilities of AngularJS and build dynamic web applications by creating customized directives with a collection of more than 30 recipes /: extend the capabilities of AngularJS and build dynamic web applications by creating customized directives with a collection of more than 30 recipes. (2015) - Monteiro, Fernando
No abstract available